Washington, D.C. - Thompson, John M. (John Milliken), 1959- (National Geographic traveler)
Detailed, informative entries on the city's main sites--including the Capitol, White House, and museum-laden National Mall--provide background information on each place, along with logistics on how best to visit. Included, too, are lesser known sites such as Dumbarton Oaks and its gorgeous gardens; bustling Eastern Market, a popular weekend brunch stop; and Frederick Douglas's former residence, Cedar Hill. Self-guided walks help you get to know different areas, including a brick sidewalk tour of stately Georgetown and a spin around the President's neighborhood.